A frame-semantic approach to conceptual metaphors in the domain of emotion - Phillip A. Neumair; Fiona M. Gehrecke; Stefan Hartmann; Alexander Ziem (Language and Cognition)
The article explores the metaphorical conceptualization of emotions. Conceptual metaphors are understood here as frames (i.e., structures of knowledge in long-term memory) in their own right. For modeling both the source and target domains of metaphors, the CoMetNet (Conceptual Metaphor Network) project uses frames documented in the German FrameNet-Constructicon project in spite of ad hoc created domains in previous literature. By doing so, it strives for a more empirically motivated description of conceptual metaphors. Drawing on a specialized corpus, it is shown that (1) our frame-semantic approach permits addressing the status of emotion concepts in the conceptual and linguistic system. More specifically, it shows that (2) frame elements (FEs) reflect adequately which aspects are relevant in the conceptualization of emotions and that (3) the complexity of emotion concepts can be thought of as an interplay between (different types of) frames. However, there are still some challenges for CoMetNet, e.g., the frame-semantic description of emotion metaphors that draw on highly schematic and scalar source domains.